Pengaruh Motivasi Kerja Dan Etos Kerja Terhadap Kinerja Guru PNS Di SMA Negeri 1 Sindangkasih - Fitriani, Zahra (Jurnal Ilmu Manajemen dan Pendidikan | E-ISSN : 3062-7788, 2025)
“This study aims to determine the influence of leadership style and work ethic on teacher performance at Sindangkasih 1 State Senior High School. The method used in this study is causality through a survey approach. In this study, the sample taken was the entire population of teachers at Sindangkasih 1 State Senior High School, the population of which was 31 teachers. The data used were primary data and secondary data. The analysis tool used in this study was multiple linear regression using SPSS 26.0. The results of the study showed that the leadership style obtained from Sindangkasih 1 State Senior High School teachers had very good criteria. The work ethic of Sindangkasih 1 State Senior High School teachers had very good assessment criteria and teacher performance at Sindangkasih 1 State Senior High School teachers had good criteria. Together, leadership style and work ethic had a significant influence on teacher performance. Partially, leadership style had a significant influence on teacher performance. Partially, work ethic had a positive and significant influence on teacher performance.”